Micro-cinema of Attraction - Stylianou-Lambert, Theopisti (My University, 2026)
Micro-cinema of attractions explores new concepts of space and time which are being formed in contemporary GIF art, focusing less on typical storytelling modes and more on GIF artworks as self-enclosed aesthetic micro-worlds.